2014
DOI: 10.1155/2014/897361
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Portuguese Propolis: The Proximity of theIn VitroDoses for Tumor and Normal Cell Lines

Abstract: With a complex chemical composition rich in phenolic compounds, propolis (resinous substance collected by Apis mellifera from various tree buds) exhibits a broad spectrum of biological activities. Recently, in vitro and in vivo data suggest that propolis has anticancer properties, but is the cytoxicity of propolis specific for tumor cells? To answer this question, the cytotoxicity of phenolic extracts from Portuguese propolis of different origins was evaluated using human tumor cell lines (MCF7—breast adenocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…The minimum obtained was recorded in the samples that contained high amounts of phenolic acids, which could be understood as a form of exo-protection. Low flavonoid concentration determined specificity, which corresponded to previous studies performed on other tumor and nontumor cells [42]. For A. linearis the balanced distribution of the two major phenolic acids corresponded to a maximum cell number.…”
Section: Determination Of Human Cell Viabilitysupporting
confidence: 82%
“…The minimum obtained was recorded in the samples that contained high amounts of phenolic acids, which could be understood as a form of exo-protection. Low flavonoid concentration determined specificity, which corresponded to previous studies performed on other tumor and nontumor cells [42]. For A. linearis the balanced distribution of the two major phenolic acids corresponded to a maximum cell number.…”
Section: Determination Of Human Cell Viabilitysupporting
confidence: 82%
“…The antiproliferative activity toward PC-3 cell line was reported in propolis from Brazil (optimal dose, 40 μg/mL) [ 50 ] and India (IC 50 , 41.8–134.5 μg/mL) [ 51 ]. The antiproliferative activity toward MCF-7 cell line was reported in propolis from Cuba (1–25 μg/mL) [ 52 ], India (13 μg/mL) [ 42 ] and (26.88–104 μg/mL) [ 51 ], Indonesia (47.45 μg/mL) [ 53 ], Java (37.8–276.45 μg/mL) [ 54 ], Malta (67 μg/mL) [ 55 ], Portugal (36–182 μg/mL) [ 56 ], and Turkey (125 μg/mL) [ 57 ]. The antiproliferative activity toward A549 cell line was reported in propolis from Cuba (IC 50 , 35.48–99.5 μg/mL) [ 58 ], India (10 μg/mL) [ 42 ], and Tunisia (200 μg/mL) [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the AChE inhibition, negative correlation between the total phenolic and flavonoids content and IC 50 was reported in propolis samples from Morocco [ 32 ]. For the antiproliferative activity toward MCF-7 cell line, negative correlation between the total polyphenol content and IC 50 was reported, whereas positive correlation between the total flavonoid content and IC 50 was reported [ 56 ]. For the antimicrobial activity, strong correlation between the total phenolic and flavonoids content and MIC was reported in propolis from Spain [ 69 ], whereas no direct correlation between them was also reported in propolis from Brazil [ 68 ] and Greece and Cyprus [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades, several studies have demonstrated the biological and pharmacological actions of different worldwide propolis samples. The following sections summarize the recent published information about antibacterial and antifungal [ 6 , 7 , 56 59 ], antiviral [ 7 , 59 , 60 ], anti-inflammatory [ 61 ], antioxidant [ 62 64 ], immunomodulatory [ 6 , 65 , 66 ], and antitumor activities [ 8 , 17 , 23 , 64 , 66 , 67 ], revealing the interest of researchers in this bee product and its potential for the development of new drugs as well.…”
Section: Biological Properties and Therapeutic Activity Of Propolimentioning
confidence: 99%